Promoting Local Culture in ELT to Enhance Students’ Character - Ridha Ilma (Jurnal Didascein Bahasa, 2016)
ABSTRACT: This paper mainly discusses about the critical analysis ofthe current practice of English language teaching which pay less attentionin local culture and also to propose the alternative solution for the sake ofsupporting and promoting character of education in Indonesia. In the lineof the national education goal, it seems that the most possible way toovercome this is by integrating Indonesian local culture values in thepractice of English Language teaching to enhance students’ character.